2023
DOI: 10.7717/peerj.14639
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of anti-diabetic medicinal plants from cells to clinical trials

Abstract: Background Diabetes is one of the fastest-growing health emergencies of the 21st century, placing a severe economic burden on many countries. Current management approaches have improved diabetic care, but several limitations still exist, such as decreased efficacy, adverse effects, and the high cost of treatment, particularly for developing nations. There is, therefore, a need for more cost-effective therapies for diabetes management. The evidence-based application of phytochemicals from plants in the manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 221 publications
0
1
0
Order By: Relevance
“…Newman et al reported that, between 1981 and 2019, there were at least 35 chemical entities identified from natural sources or modified/synthetized based on natural products that have potential use in the treatment of diabetes [ 1 ]. Specifically, plants have proven to be interesting sources of natural products with effective mechanisms of action for the management of diseases such as diabetes [ 2 ]. In fact, the use of 1300 plant species for the treatment of this disease worldwide have been reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Newman et al reported that, between 1981 and 2019, there were at least 35 chemical entities identified from natural sources or modified/synthetized based on natural products that have potential use in the treatment of diabetes [ 1 ]. Specifically, plants have proven to be interesting sources of natural products with effective mechanisms of action for the management of diseases such as diabetes [ 2 ]. In fact, the use of 1300 plant species for the treatment of this disease worldwide have been reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%